Epileptic seizures detection and the analysis of optimal seizure prediction horizon based on frequency and phase analysis - Jiang, Ximiao; Liu, Xiaotong; Liu, Youjun; Wang, Qingyun; Li, Bao; Zhang, Liyuan (Frontiers in Neuroscience, 2023)
Changes in the frequency composition of the human electroencephalogram are associated with the transitions to epileptic seizures. Cross-frequency coupling (CFC) is a measure of neural oscillations in different frequency bands and brain areas and specifically phase-amplitude coupling (PAC), a form of CFC, can be used to characterise these dynamic transitions. In this paper, we propose a method for seizure detection and prediction based on frequency-domain analysis and PAC combined with machine learning. We analyzed two databases, the Siena Scalp EEG database and the CHB-MIT database, and used the frequency features and modulation index (MI) for time-dependent quantification. The extracted features were fed to a random forest classifier for classification and prediction. The seizure prediction horizon (SPH) was also analyzed based on the highest-performing band in order to maximise the time for intervention and treatment while ensuring the accuracy of the prediction. Under comprehensive consideration, the results demonstrate that better performance could be achieved at an interval length of 5 minutes with the average accuracy of 85.71% and 95.87% for the Siena Scalp EEG database and the CHB-MIT database, respectively. As for the adult database, the combination of PAC analysis and classification can be of significant help for seizure detection and prediction. It suggests that the rarely used SPH also has a major impact on the seizure detection and prediction and further explorations for the application of PAC are needed.